El discurso metafórico en la poesía erótica de Carlos Germán Belli - Mautino Guillén, Alejandro Giancarlo (2020)
In this article we analyze the fundamental function that metaphorical elements have in the construction of erotic discourse in the poetry of Carlos Germán Belli. From our perspective, the metaphors and the swallowing and vigilant discourses in his poetry construct a singular reflection on the daily routine of the erotic act through the body. For this purpose we rely on neorethoric and cognitive linguistics to understand the relationship between thought-language linked to erotic poetic discourse in some poems by the author of Sextinas y otros poemas (1970).